Impacto del sistema transmilenio en el espacio público: estación héroes 2000-2016 (2017)
The research is focused in reflect how the infrastructure of transport mass modify the conditions of use in the space public. For this research is takes emphasizing, the station of Transmilenio of the street 80, station Heroes, and from there is performed a study referential exploratory of them authors that have developed this thematic, in addition to analyze the impact that have them flows pedestrian of the system of transport in the space public, to study.